Effect of Heat Treatment on Quality of Refrigerated Fresh-cut Cherry Peppers - Avalos Llano, Karina R.; Sgroppo, Sonia C.; Chaves, Alicia R. (Agrociencia Uruguay, 2012)
The effect of applying a heat treatment (55 ºC for 60 s) on the evolution of quality parameters of fresh-cut (without the core) peppers (Capsicum annuum, L. cv cherry) stored for 15 days at 10 ºC in crystal polyethylene terephthalate (PET) trays covered with PVC film was studied. During this period, general appearance of the fruit, development of fungi, respiration rate, titratable acidity, pH and total sugar content were evaluated. Results showed that treated samples displayed a better general appearance and lower fungal decay than control fruit at the end of storage. Immediately after heat treatment, no differences in respiration rate values between control and treated fruit were found. However, treated peppers displayed lower respiratory activity than controls during storage. The heat treatment did not affect acidity and pH, and total sugar values were slightly lower than in control fruit. We conclude that treatment at 55 ºC for 60 s reduced fungal attack and maintained de-cored cherry peppers quality during storage at 10 ºC.